2019
DOI: 10.3847/1538-4357/ab041f
|View full text |Cite
|
Sign up to set email alerts
|

Galactic Cosmic-Ray Anisotropies: Voyager 1 in the Local Interstellar Medium

Abstract: Since crossing the heliopause on August 25, 2012, Voyager 1 observed reductions in galactic cosmic ray count rates caused by a time-varying depletion of particles with pitch angles near 90°, while intensities of particles with other pitch angles remain unchanged. Between late 2012 and mid-2017, three large-scale events occurred, lasting from ~100 to ~630 days. Omnidirectional and directional high-energy data from Voyager 1's Cosmic Ray Subsystem are used to report cosmic ray intensity variations. Omnidirection… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 30 publications
5
36
0
Order By: Relevance
“…Interestingly, we find that the optimum Voyager 1 start time occurred on DOY 331 of 2012very near to the arrival of the shock observed by MAG (roughly DOY 335; . This is physically consistent with the idea that most VLISM anisotropies form via particle trapping and energy loss in the adiabatically-expanding fields of the shocked plasma downstream (Kóta & Jokipii 2017;Rankin et al 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, we find that the optimum Voyager 1 start time occurred on DOY 331 of 2012very near to the arrival of the shock observed by MAG (roughly DOY 335; . This is physically consistent with the idea that most VLISM anisotropies form via particle trapping and energy loss in the adiabatically-expanding fields of the shocked plasma downstream (Kóta & Jokipii 2017;Rankin et al 2019).…”
Section: Discussionsupporting
confidence: 88%
“…IBEX regularly observes time variation in the morphology of the globallydistributed flux (see e.g., Schwadron et al 2018 for the first 9 years of LOS-integrated pressure observations), and the Voyagers have a long history of measuring MIRs, GMIRs, and other transient disturbances in situ at their various locations through the heliosphere and beyond (e.g., McDonald et al 1981;Burlaga et al 1985;Gurnett et al 1993;Whang & Burlaga 1995;Burlaga & Ness 1998;Paularena et al 2001;Burlaga et al 2003;Richardson et al 2006;Webber et al 2009;Burlaga et al 2011;Luo et al 2011). In addition to the 2012 events used in this study, Voyager 2 observed several GMIRs and MIRs in the heliosheath from 2015 to 2018 (e.g., Burlaga et al 2018aBurlaga et al , 2019, and Voyager 1 measured larger, more extended GCR anisotropy episodes starting in 2015 (e.g., Rankin et al 2019) and 2018. Likewise, IBEX has now collected 10 years of data.…”
Section: Discussionmentioning
confidence: 65%
“…The first quantitative, physical interpretation of the anisotropy was given by Roelof et al (2013): "[T]ime-dependent depletions in the intensities localized in pitch angle near 90°...would be observed whenever [Voyager 1] is located between (at least) two compressions of the magnetic field on a field line, both (distant) ends of which contain equal isotropic GCR intensities....These compressions would, by their very nature, be time dependent, thus explaining the time dependence of our observed [pitch angle distribution] anisotropies." This twocompression, trapped configuration view has informed subsequent investigations of the V1 GCR anisotropies, including theoretical work by Kóta & Jokipii (2017) and a recent observational study by Rankin et al (2019), with considerable success. The anisotropic variations have been compared with in situ interstellar shocks and radio measurements of plasma oscillations (Gurnett et al 2015), but the unusual timing of the cosmic ray anisotropy periods relative to the magnetic field, plasma waves, and locally accelerated particles calls for an explanation.…”
Section: Introductionmentioning
confidence: 91%
“…It prevents GCRs traveling in the opposite direction from reflecting back toward V1 and filling in the ∼90°pitch angles, and therefore it explains the observed anisotropy (Figure 6). Rankin et al (2019) found this mechanism to be effective. They conducted an analysis of the anisotropies observed at V1 using the CRS instrument.…”
Section: Cosmic Rays In the Lismmentioning
confidence: 98%
See 1 more Smart Citation